The Role and Function of Universiti Kebangsaan Malaysia Permanent Forest Reserve in Research and Education - Mat Salleh, Kamarudin (Universiti Putra Malaysia Press, 1999)
The UKM Permanent Forest Reserve is an area within the main campus of UKM in Bangi, developed in an area formerly known as Bangi Forest Reserve (BFR). This 138 ha (340 acres) of recovering logged-over forest, inclusive of some 81 ha of ecological research area was formally gazetted in 1993 as UKM Permanent Forest Reserve to safeguard and prevent further development of this green area. This was further reiterated in the UKM Sustainable Forest Policy which was introduced in 1997. The BFR was part of what was used to be known as Langat Basin Forest area which is now very much fragmented into various pieces of small left-overs. The close vicinity of the forest to the campus has been one of the main reasons for the extensive utilisation of the area for student research projects. Since the early days of its development, the planners of UKM have envisaged holistic concept of having the campus to resemble a botanic garden as a whole to serve as living laboratories for the use of UKM students in education and research. As a result, UKM has set an example and currently hold one of the best germplasm collections of ornamental plants, especially palms and ferns collections in Malaysia. The UKM Permanent Forest Reserve is an important carbon sink green area in the Langat Basin as well as a biological laboratory and open classroom for UKM students.